Lionel goes ape - Griff (Kent : ticktock, 2001)
A boy named Stanley begins to wonder if an ape might make a better sibling than his older brother, Lionel.
"First published in Great Britain in 2001 by ticktock Publishing Ltd."--T.p. verso.
Cover title: Stanley goes ape.
2.7
K-3
Keywords: Apes -- Fiction; Brothers -- Fiction